School-Based Interventions for Reducing Youths' Racial and Ethnic Prejudice. (October 2019) - Grapin, Sally L.; Griffin, Charity B.; Naser, Shereen C.; Brown, Jeffrey M.; Proctor, Sherrie L.
Minoritized youth encounter racial and ethnic prejudice and discrimination in a variety of settings, including schools. Prejudice refers to harboring negative attitudes and beliefs toward targeted social groups; discrimination reflects translating those attitudes into actions that marginalize targeted groups. Exposure to racial and ethnic discrimination has been associated with numerous detrimental outcomes for youth, including poorer mental health outcomes and lower levels of academic performance. This article describes the nature of racial and ethnic discrimination encountered by minoritized youth as well as its impact on these populations. It also reviews research on prejudice reduction interventions for youth, with a focus on those interventions designed for school settings. In light of existing research, several policy recommendations support high-quality, evidence-based programming in schools.